Hydrogen production by immobilized cells of unicellular halotolerant cyanobacterium aphanothece halophytica in alginate beads - Pansook, Sunisa; Incharoensakdi, Aran; Phunpruch, Saranya (Asia-Pacific Journal of Science and Technology, 2016)
Hydrogen is an interesting alternative energy carrier that can be produced by various kinds of cyanobacteria. The unicellular halotolerant cyanobacterium Aphanothece halophytica is one of the potential cyanobacterial candidates for H2 production. Its dark fermentative H 2 production is catalyzed by bidirectional hydrogenase activity through the catabolism of storage glycogen. This work aimed to study H2 production by A. halophytica cells immobilized in alginate beads. The result showed that under nitrogen deprivation H2 production by the immobilized cells of A. halophytica in alginate cells was obviously higher than that of free cells. The highest H2 production was found in immobilized cells prepared from 4.5 % (w/v) sodium alginate in 100 mM calcium chloride. Finally, H2 production yield of 50 immobilized cell beads per 20 mL glass vial was higher than of 100 and 150 immobilized cell beads.<br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;">